By Our Own Hands : The Women Artist's Movement Southern California 1970-1976 - Wilding, Faith (Santa Monica : Double X Inc., 1977)
Rosenbach, Ulrike ; Chicago, Judy ; Schapiro, Miriam ; Wayne, June ; Hall, Vicki ; Kozloff, Joyce ; Rush, Christine ; Lacy, Suzanne ; Antin, Eleanor ; etc.
boek
Keywords: Wilding, Faith